The Influence of Green Marketing and Brand Awareness on Purchase Intention Through Brand Image as a Mediation Variable - Murtiningsih, Dewi; Wulandari, Ririn; Mulyaningsih, Hendrati Dwi (Universitas Mercu Buana, 2024)
Marketing using the concept of green marketing should create positive emotions so that consumers can influence product evaluation. Objectives: The problems of the study are: Does green marketing influence brand image? Does green marketing influence buying interest through brand image as a mediation variable? Does brand awareness influence buying interest? Does brand awareness influence brand image? Does brand awareness influence purchasing attention through the perception of a brand as a mediation variable? Does brand image influence buying interest? Meanwhile, the objectives of the study are to find out the influence of green marketing on buying interest, the influence of green marketing on brand image, the influence of green marketing on buying interest through brand image as a mediation variable, the brand awareness's impact on consumers' purchase intentions, the impact of brand awareness on brand image, the influence of buying interest through brand image as a mediation variable, and the influence of brand image on buying interest.Methodology: This research is part of exploration research. Participants in the research are unknown; the quantity of samples used in this research is 110. The analysis tool used is PLS.Finding: green marketing does not influence buying interests; green marketing does not influence brand image; brand image does not moderate the impact of green advertising on buying interests; brand awareness influences buying interests; brand awareness influences brand image; brand image does not mediate the impact of brand recognition on purchasing interests; and trademark image influences purchasing interests. Conclusion: Based on the findings from the conclusions of this study, these are some suggestions that can be used as research recommendations: this research focuses on the variables green marketing, brand awareness, brand image, and buying interest, so other variables such as brand trust, social media marketing, perceived quality, price, and customer satisfaction are needed to find out the buying interest; Future studies are anticipated to increase the sample size, expand the research object, and add relevant topics; future research is expected to process data with different analysis tools.